Taxonomy, phylogeny and stratigraphical ranges of middle Permian pareiasaurs from the Karoo Basin of South Africa. (2nd October 2021) - Van den Brandt, Marc J.; Abdala, Fernando; Benoit, Julien; Day, Michael O.; Groenewald, David P.; Rubidge, Bruce S.
Abstract : Pareiasaurs were relatively abundant, globally-distributed, herbivorous parareptiles of the mid to late Permian. The basal-most forms, all members of the Bradysauria, are restricted to the Guadalupian (mid-Permian) of South Africa and went extinct in the late Capitanian near the top of the Tapinocephalus Assemblage Zone. Currently four species are recognized in this group: Bradysaurus seeleyi, B. baini, Embrithosaurus schwarzi and Nochelesaurus alexanderi . These taxa have been poorly defined historically and based on a limited number of specimens, leaving the taxonomic diversity of the group open to doubt and limiting their utility in biostratigraphy. Here, we present our fourth and final contribution to improve the understanding of this group by providing a taxonomical and phylogenetic review, updated stratigraphical ranges, and updated diagnoses for each taxon within Bradysauria. Bradysaurus seeleyi is synonymized with Bradysaurus baini, resulting in three valid mid-Permian pareiasaur taxa: Bradysaurus baini, Embrithosaurus schwarzi and Nochelesaurus alexanderi . Our cladistic analysis of cranial and postcranial characters supports the monophyly of Bradysauria with five synapomorphies. Embrithosaurus schwarzi is recovered as the sister taxon to a clade containing Bradysaurus baini and Nochelesaurus alexanderi . By identifying 157 pareiasaur specimens in fossil collections we show that the Bradysauria are stratigraphically restricted to the Abrahamskraal Formation of the Beaufort Group and suggest a staggered appearance. Bradysaurus baini is first to appear, followed by Nochelesaurus alexanderi, and lastly by Embrithosaurus schwarzi . All three taxa perished during the Capitanian mass extinction, and have their highest occurrences near the top of the Abrahamskraal Formation.